Fiscal and monetary responses to the COVID-19 pandemic: Current conditions and future scenarios in developing countries - Díaz-Bonilla, Eugenio; Centurión, Miriam (International Food Policy Research Institute, 2022)
Our 2020 report on responses to COVID-19 discussed national pandemic response plans in developing countries (Díaz-Bonilla 2020). Those integrated plans, it was argued, would require a centralized crisis-management office led by the president, prime minister, or equivalent, with participation of the relevant public and private sector representatives. A strong fiscal and monetary response was needed to support these plans, including unconventional monetary policies, such as those used by what were labeled “developmental central banks” during the 1960s and 1970s (Díaz-Bonilla 2015). Expansion in money supply during the pandemic would finance the fiscal deficit related to public expenditures on health and non-health programs as well as programs to maintain private sector production. We noted that central banks in developed countries have followed a similar monetary approach, now called “quantitative easing,” since the 2008–2009 financial crisis, an approach they ramped up during the pandemic.